2020
DOI: 10.1177/1352458520912172
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of diffusely abnormal white matter to focal lesions is linked to progression in secondary progressive multiple sclerosis

Abstract: Background: Diffusely abnormal white matter (DAWM) regions are observed in magnetic resonance images of secondary progressive multiple sclerosis (SPMS) patients. However, their role in clinical progression is still not established. Objectives: To characterize the longitudinal volumetric and intensity evolution of DAWM and focal white matter lesions (FWML) and assess their associations with clinical outcomes and progression in SPMS. Methods: Data include 589 SPMS participants followed up for 3 years (3951 time … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 37 publications
2
23
0
Order By: Relevance
“…3 A 3-year longitudinal study in secondary progressive MS has shown that the development of lesions in DAWM regions is associated with clinical progression. 13 Quantitative MRI measures of DAWM in relapsing remitting, primary progressive and secondary progressive MS demonstrate abnormalities in magnetization transfer ratio, myelin water fraction, fractional anisotropy, mean diffusivity, and T 1 relaxation time, with values of these metrics typically between those of T 2 lesions and NAWM. 7,[9][10][11][12]14,15 DAWM has not been systematically described at the earliest stage of MS, known as clinically isolated syndrome (CIS).…”
Section: Introductionmentioning
confidence: 98%
“…3 A 3-year longitudinal study in secondary progressive MS has shown that the development of lesions in DAWM regions is associated with clinical progression. 13 Quantitative MRI measures of DAWM in relapsing remitting, primary progressive and secondary progressive MS demonstrate abnormalities in magnetization transfer ratio, myelin water fraction, fractional anisotropy, mean diffusivity, and T 1 relaxation time, with values of these metrics typically between those of T 2 lesions and NAWM. 7,[9][10][11][12]14,15 DAWM has not been systematically described at the earliest stage of MS, known as clinically isolated syndrome (CIS).…”
Section: Introductionmentioning
confidence: 98%
“…51 All segmentations were then visually assessed, and BISON tissue classification results passed quality control for all timepoints. 48 The successful application of BISON in other data sets with different imaging characteristics and underlying pathologies further validates its robustness and domain adaptability.…”
Section: Discussionmentioning
confidence: 74%
“…In addition to the Human Phantom data set, BISON has also been used to perform tissue classification on other data sets, [48][49][50][51] including data from a multicenter and multiscanner (20 different scanner models from four manufacturers, including both 1.5T and 3T scanners) clinical trial of 589 patients with secondary progressive multiple sclerosis (3951 timepoints), 48 as well as a data set of patients with pediatric-onset acquired demyelinating syndrome. 51 All segmentations were then visually assessed, and BISON tissue classification results passed quality control for all timepoints.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21,22 However, lesions do develop in areas of DAWM, suggesting that DAWM can be an area within which active pathology can arise, which could confound in vivo and postmortem observations. 21,45 The "inside-out hypothesis" of the pathogenesis of…”
Section: Potential Pathophysiological Mechanisms Of Dawm In Multiple Sclerosismentioning
confidence: 99%